Rise of the school for good and evil eaudiobook - Chainani, Soman (The School for Good and Evil, 2022)
THE SCHOOL FOR GOOD AND EVIL is the #1 movie now streaming on Netflix—starring Academy Award winner Charlize Theron, Kerry Washington, Laurence Fishburne, Michelle Yeoh, Sofia Wylie, Sophie Anne Caruso, Jamie Flatters, Earl Cave, Kit Young, and many others! The battle between Good and Evil begins. Two brothers. One Good. One Evil. Together they watch over the Endless Woods. Together they choose the students for the School for Good and Evil. Together they train them, teach them, prepare them for their fate. Then, something happens. Something unexpected. Something powerful. Something that will change everything and everyone. Who will survive? Who will rule the School? The journey starts here. Every step is filled with magic, surprises, and daring deeds that test courage, loyalty, and who you really are. But they only lead you to the very beginning of the adventures that are THE SCHOOL FOR GOOD AND EVIL.